Mourning becomes the law : philosophy and representation - Rose, Gillian (Cambridge University Press, 1996)
In Mourning Becomes the Law, Gillian Rose takes us beyond the impasse of post-modernism or 'despairing rationalism without reason'. Arguing that the post-modern search for a 'new ethics' and ironic philosophy are incoherent, she breathes new life into the debates concerning power and domination, transcendence and eternity.